Coronavirus disease COVID-2019 - B. K. Romanov (Безопасность и риск фармакотерапии, 2020)
The paper presents data on the coronavirus diseaseCOVID-2019 caused by the SARS-CoV-2 coronavirus, which was temporarily named 2019-nCoV (2019 novel coronavirus) until 11 February 2020. An outbreak of pneumonia of unknown etiology in Wuhan (Hubei province of China) which was first described in an official publication of the Chinese Office of the World Health Organization on December 31, 2019, attracted attention of both dedicated experts and the entire international community. On January 30, 2019 it was recognised as a public health emergency of international concern. The first cases were reported on December 12, 2019 in China, and on January 31, 2020 Russia reported its first two cases of the infection in two Chinese citizens staying in Russia. The causative agent is the new SARS-CoV-2 coronavirus. It had not been detected before, and was first identified by Chinese researchers on January 7, 2020 under the temporary name 2019-nCoV. The aim of the study was to summarise information about coronavirus diseaseCOVID-2019 beginning from the onset of the epidemic until early March 2020. The paper provides general information about coronaviruses, developments of the COVID-2019 epidemic caused by the SARS-CoV-2 coronavirus, and gives an assessment of the global epidemiological situation. It cites the recommendations of national regulatory authorities and the World Health Organization on the treatment of various forms of coronavirus infection and septic shock caused by SARS-CoV-2, including target values of systemic hemodynamics, a list of recommended medicines, methods of their use, and limitations of pharmacotherapy.